Failure analysis of punches and investigation notch impact strength of tool steel cryogenic treated with tempering used in hot forging - KAYNAK, YUSUF (My University, 2023)
Plumbing systems, valves, fittings, condensers, pipes, and other hot-forming components are produced using hot forging, a type of plastic deformation. This method may result in equipment damage due to dies operating under high-temperature conditions, punches breaking, and other issues. The short life of the dies used in forging operations is a longstanding problem for the mass production. To increase the life of die steels, there are continuing attempts to increase the toughness, including heat treatments. In this study, both cryogenic and heat treatments were applied to Dievar,DIN-1.2367 hot work tool steels. The resulting samples obtained were examined in terms of their high temperature and room temperature impact resistance. Observations have shown that operating temperatures significantly affect the impact strength of the material. The study also revealed the direct relation between punch life in mass prodcution condition and tougness. Macroscopic and microscopic examinations were used to examine the crack structures carefully.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; ENGINEERING, MANUFACTURING; Metaller ve Alaşımlar; Fizik Bilimleri; Endüstri ve İmalat Mühendisliği; Metals and Alloys; Physical Sciences; Industrial and Manufacturing Engineering; brass alloy; cryogenic treatment; Failure analysis; hot forging; microstructure; punch; Failure analysis; microstructure; hot forging; punch; brass alloy; cryogenic treatment